2022
DOI: 10.5267/j.jfs.2022.8.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of wildfires in a sustainable future

Abstract: Climate change and global warming have led to many risks and changes for the Earth, including the increase in natural fires, floods, air pollution, unusual seasons, etc. The increase in the trend of global warming may bring many countries underwater. For instance, the populous Asian nation of Bangladesh is most vulnerable to rising sea levels. It is estimated that a rise of just one meter in sea level is enough to submerge 30,000 square kilometres of the coastal areas of Bangladesh and displace 15 million peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…• Energy efficiency: Cloud data centers are typically more energy-efficient than on-premises data centers, as they can take advantage of economies of scale to optimize their energy usage (Sharifi, 2022).…”
Section: Sustainable Development Of Cloud Computingmentioning
confidence: 99%
“…• Energy efficiency: Cloud data centers are typically more energy-efficient than on-premises data centers, as they can take advantage of economies of scale to optimize their energy usage (Sharifi, 2022).…”
Section: Sustainable Development Of Cloud Computingmentioning
confidence: 99%
“…Increased global warming, a trend that has been a result of human activity since the mid-20th century, has already led to an increase in the frequency and severity of fire weather worldwide, increasing the risk of wildfires (Jones et al, 2020;Sharifi, 2022). Previous studies have shown that climate change will increase the risk of wildfires, with a global increase in average temperatures; frequency and intensity/extent of heatwaves, and regional increases in the duration, intensity and frequency of droughts, have the potential to influence fire weather, and thus increase the ignition potential of wildfires (Jones et al, 2020;Sharifi, 2022). The potential of wildfire occurrence is increasing at an unprecedented rate, possibly comparable to the rapid climatic changes affecting Earth's ecosystems in its geological past.…”
Section: Introductionmentioning
confidence: 99%
“…The two examples discussed in this study highlight the interplay between wildfires and a wide range of environmental and climatic change processes in the Earth's surface systems, which is critical to the complete understanding of the feedback effects of wildfires and their changes on terrestrial ecosystems over various time scales. In modern ecosystems, global warming and drought-induced climate conditions triggered by high levels of anthropogenic greenhouse gas emissions pose several risks to the Earth's environment (Sharifi, 2022). In particular, these issues have the potential to increase the probability of widespread natural fires, which have a significant impact on plants, animals, and other natural resources worldwide (Sharifi, 2022).…”
mentioning
confidence: 99%
See 2 more Smart Citations